Acute Motor Axonal Neuropathy in Association with Hepatitis E - Al-Saffar, Araz; Al-Fatly, Bassam (Frontiers in Neurology, 2018)
Guillain-Barré syndrome is an acute peripheral neuropathy that develops as a result of post-infectious immune mediated nerve injury. It can be classified into classic and variant Guillain-Barré syndrome. Acute motor axonal neuropathy is a subtype of Guillain-Barré syndrome with the key clinical features of pure motor weakness, areflexia, absence of sensory symptoms and lack of neurophysiologic evidence of demyelination. We reported the first case of acute motor axonal neuropathy in association with hepatitis E infection. A young woman was referred to us after a period of nausea, fever and diarrhea. She had unexplained muscle weakness at admission, and has been diagnosed with acute hepatitis E infection. A rigorous clinical neurological assessment revealed bilateral symmetrical weakness, which affects the lower more than the upper limbs, with no evidence of sensory involvement. Neurophysiological measurements indicated acute axonal injury without clues to demyelination. A diagnosis of acute motor axonal neuropathy subtype has been made, to which she only received supportive therapy. The symptoms resolved spontaneously and full recovery of motor function was attained after 35 days of weakness onset with complete normalization of neurophysiologic parameters.